Students’ expectations and motivation for service-learning in public relations - Muturi, Nancy W.; An, Soontae; Mwangi, Samuel (My University, 2014)
This study is based on a survey of public relations students and examines their attitudes, expectations, and motivations for participating in curriculum-infused service-learning projects. Results indicate that prior participation does not influence attitudes or expectations, but motivation to participate in the project was significantly associated with positive attitude and higher expectations. Students’ expectations, which include social and professional growth, and psychological and altruistic gratification through community contributions, indicate a need for discipline-focused service-learning programs and for a focus on civic engagement given the role of public relations in relationship building and in strategically addressing social issues that impact society.
Keywords: Service-learning; Public relations; Motivation; Attitudes; Expectations